Innate Immune Responses to AAV Vectors - Rogers, Geoffrey L.; Martino, Ashley T.; Aslanidi, George V.; Jayandharan, Giridhara R.; Srivastava, Arun; Herzog, Roland W. (Frontiers in Microbiology, 2011)
Gene replacement therapy by in vivo delivery of adeno-associated virus (AAV) is attractive as a potential treatment for a variety of genetic disorders. However, while AAV has been used successfully in many models, other experiments in clinical trials and in animal models have been hampered by undesired responses from the immune system. Recent studies of AAV immunology have focused on the elimination of transgene-expressing cells by the adaptive immune system, yet the innate immune system also has a critical role, both in the initial response to the vector and in prompting a deleterious adaptive immune response. Responses to AAV vectors are primarily mediated by the TLR9 MyD88 pathway, which induces the production of proinflammatory cytokines by activating the NF κB pathways and inducing type I IFN production; self-complementary AAV vectors enhance these inflammatory processes. Additionally, the alternative NF κB pathway influences transgene expression in cells transduced by AAV. This review highlights these recent discoveries regarding innate immune responses to AAV and discusses strategies to ablate these potentially detrimental signaling pathways.